Protein Conformantional Search Using Bees Algorithm - Bahamish, Hesham Awadh A.; Abdullah, Rosni; Salam, Rosalina Abdul (2008)
Proteins perform many biological functions in the human body. The structure of the protein determines its function. In order to predict the protein structure computationally, protein must be represented in a proper representation. To this end, an energy function is used to calculate its energy and a conformational search algorithm is used to search the conformational search space to find the lowest free energy corformation.